Relação entre depressão, estado nutricional e fatores associados em idosos usuários do serviço público de saúde na cidade de Itaqui/RS - (:unkn) unknown (Universidade Federal do Pampa, 2018)
This is a cross-sectional, analytical and descriptive study carried out in the city of Itaqui / RS, which aimed to evaluate the relationship between the presence of depressive symptoms, nutritional status and associated factors in elderly public health service users, who seek care Cheers. The sample is made up of people 60 years of age and older who were interested in participating in the research. The collections occurred at the points where the elderly sought care or wanted care to improve health conditions, such as ESF’s and the city's central health post. The questionnaire covered socioeconomic and sociodemographic issues, which were opened and closed, and questions were asked about the presence of diseases and health conditions. The nutritional assessment was performed through weight, height, and from these data, the body mass index was calculated. The questionnaire was applied with the Yesavage Geriatric Depression Scale. This study was submitted to the Research Ethics Committee of the Federal University of Pampa. It was observed that ¾ of the elderly were in economic class D / E, and had low schooling. 51% were overweight / obese, and in 86% of them depressive symptoms were absent. It is concluded with the present study that the majority of the elderly were in socioeconomic vulnerability, classified as overweight and without the presence of depressive symptoms. No associations were found between nutritional status, depressive symptoms and associated life factors.
Keywords: Estado depressivo; Déficit nutricional; Pessoas idosas e saúde pública; Depressive state; Nutritional deficit; Elderly people and public health; CNPQ::CIENCIAS DA SAUDE